STRATEGI KORAN KALTIM POST DALAM MENARIK PEMBACA DI ERA DIGITAL: Strategi Koran Kaltim Post Dalam Menarik Pembaca Di Era Digital - Arianti Hasanah; Sabiruddin Sabiruddin (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
This study aims to find out the strategies used by Kaltim Post in order to attract readers in the digital era. This research was conducted using a descriptive qualitative method to describe the efforts and forms of strategy taken by Kaltim Post in responding to changes in people's reading practices, from the conventional era to the digital era. This study uses two data sources, namely primary data sources from direct interviews with the leadership of Kaltim Post and secondary data sources. Data collection in this study was carried out by means of observation and interviews. The validity of the data in this study used two triangulations, namely triangulation of data sources and triangulation of methods. The results of this study indicate that the strategies carried out by Kaltim Post in the digital era are four things. First, innovation in content quality by utilizing digital platforms and preparing a Quick Response (QR) code. Second, carry out convergence-based promotions by regularly updating information on social media and cooperating. The third is the location considerations for distributing the circulation of the Kaltim Post newspaper. Lastly, use a progressive pricing system.